Pemberdayaan Aparatur di Kelurahan Malalayang Dua Kecamatan Malalayang Kota Manado - Kapoh, Winsy Jerry; Liando, Daud M; Rares, Joice J (JURNAL ILMIAH SOCIETY, 2016)
Empowerment is an effort to improve the capabilities and potential of the community, so that people can realize the identity, status and dignity to the maximum to survive and develop themselves independently in economic, social, religious and cultural. Government officials today are required to provide the best service for the community, especially in the public service, but the reality in some places one in the village Malalayang Dua subdistrict Malalayang, resource quality apparatus is still questionable it is certainly an impact on excellent service.This study reviews the empowerment for the apparatus in two districts Malalayang Malalayang village, using qualitative research methods, the results of research low levels of education and infrastructure are less likely to cause low quality of village officials so requires empowerment of the above organizations.